Q: How do you make 24 using 5 2 9 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

(-7 -9)*(-3)/2 = (-16)*(-3)/2 = 48/2 = 24

9 - 1 = 8 2 + 1 = 3 8 x 3 = 24

(9 - 6)*4*2 = 3*4*2 = 12*2 = 24

2*(1 + 3!) + 4! = 2*(1 + 6) + 24 = 2*7 + 24 = 14 + 24 = 38

8*3*(4-3) = 24

Related questions

It could be: ((3*2)-2)*6 = 24

12 ÷ (3 - 5/2) = 12 ÷ 1/2 = 24

One way: ((2 * 5) - 2) * 3 = 24

21+3 or using all the numbers: 21 + (3*(2-1))

2 - 1 = 1 1 x 3 = 3 3 x 8 = 24

(-7 -9)*(-3)/2 = (-16)*(-3)/2 = 48/2 = 24

Yes. 6*(5 - 3)*2 = 6*2*2 = 12*2 = 24

Assuming all of {7, 8, 2, 3} have to be used exactly once: (8 - 2) x (7 - 3) = 24.

By using: (3*6)+(3*2) = 24

5! / 4 - 2 * 3

9 - 1 = 8 2 + 1 = 3 8 x 3 = 24

6 x (6/3 + 2) = 6 x (2 + 2) = 6 x 4 = 24